Transforming the public provision of training: reorganisation or privatisation? : Long-term changes in Sweden and the Netherlands ; discussion dossier - Westphalen, Sven-Age [Mitarbeiter]; Brandsma, Jittie [Mitarbeiter]; Noonan, Richard [Mitarbeiter] (Office for Official Publications of the European Communities, 2000)
"The public sector is undergoing radical changes due to internal as well as external pressure to increase efficiency. Consequently, the public sector is becoming less concerned with who is providing a given service while becoming more concerned about the quality, reliability, accessibility and price of the service in question. New management strategies are therefore being introduced, and public organisations are becoming streamlined or even privatised. This report examines some of these changes specifically within the Netherlands and Sweden. The Dutch analysis focuses on the organisational changes and the rationale behind them, while the Swedish analysis focuses more on the political processes. The corporatisation of the Swedish public training provision system, the Amu-Gruppen, is a clear example of deregulation and market orientation of a former, highly public body with an almost monopolistic position. The establishment of regional training centres (ROCs) in the Netherlands, which has resulted in a drop of publicly funded VET institutions from 396 to 65 institutions, is an example of the reorganisation of public organisations." (Autorenreferat, BIBB-Doku)
Keywords: Berufsbildung; Ausbildungsplatzangebot; Bildungssteuerung; Bildungsfinanzierung; Berufsbildungspolitik; Niederlande; Schweden